Expression of FOXO6 is Associated With Oxidative Stress Level and Predicts the Prognosis in Hepatocellular Cancer: A Comparative Study. Issue 21 (May 2016) - Chen, Hai-Yong; Chen, Yao-Min; Wu, Jian; Yang, Fu-Chun; Lv, Zhen; Xu, Xiao-Feng; Zheng, Shu-Sen
Abstract : Abstract: The aim of this study was to explore the association of Forkhead box O6 (FOXO6) expression with oxidative stress level and prognosis of hepatocellular cancer (HCC). The case group included tissues of HCC from 128 patients who were hospitalized in Division of Hepatobiliary and Pancreatic Surgery, Department of Surgery of First Affiliated Hospital, School of Medicine, Zhejiang University. The control group included normal liver tissues from 74 patients. RT-PCR and Western blot were used to test expressions of FOXO6, heme oxygenase (HO)-1, glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT). Dihydroethidium (DHE) was dyed to observe reactive oxygen species (ROS) level. Immunohistochemistry was used to test FOXO6 expression. FOXO6 was silenced in HepG2 cells to detect cell proliferation and apoptosis. The expressions of ROS, HO-1, GPx, SOD, CAT, p27, and cyclin D1 were also detected to further explore the possible mechanism. The expressions of FOXO6, HO-1, GPx, SOD, and CAT in HCC tissue was significantly higher than those in normal and adjacent HCC tissues ( P  <0.05). The tumor size, TNM stage, Alpha-fetoprotein( AFP) level, the presence or absence of hepatitis B surface antigen (HbsAg), and differentiation degree were related to FOXO6 expression level (all P  <0.05). COX analysis showed that high FOXO6 expression, male, positive HBsAg, advanced TNM staging, high expression of AFP, and low degree of differentiation were all risk factors for prognosis in HCC ( P  <0.05). Compared with the blank group (C group, without transfection) and the negative control (NC) group, the mRNA expressions of ROS, FOXO6, HO-1, SOD, GPx, and CAT were decreased ( P  <0.05). si-RNA group had significantly decreased proliferation speed during 24 to 72 hours ( P  <0.05), whereas si-FOXO6 group had remarkably increased G0/G1 staged cells and decreased S-staged cells ( P  <0.05). The si-FOXO6 group showed notably increased apoptosis rate ( P  <0.05) and p27 expressions as well as decreased cyclin D1 expressions ( P  <0.05). FOXO6 was highly expressed in HCC tissue and was related to oxidative stress levels. Furthermore, FOXO6 expression can be used as a biomarker for deterioration and prognosis of liver cancer, which may provide a novel treatment target for HCC therapy.